2007
DOI: 10.1007/s00223-006-0155-7
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Effects of Visfatin on Human Osteoblasts

Abstract: Visfatin (also known as pre-B cell colony-enhancing factor or PBEF) is a novel adipocytokine that is highly expressed in visceral fat and upregulated in obesity and type 2 diabetes mellitus. Visfatin binds to and activates the insulin receptor (IR), thereby exerting insulin-mimetic effects in various cell lines. IR has been detected in osteoblasts, which is consistent with the role of insulin as an important osteotropic hormone. This study investigated the actions of visfatin on human primary osteoblasts. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
158
3
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(172 citation statements)
references
References 43 publications
5
158
3
6
Order By: Relevance
“…Higher adipocytokine levels were found among women with larger osteophytes (>10 mm) than in those with no or smaller osteophytes (<10 mm) [70]. Visfatin has been also found to influence osteoblasts proliferation and type II collagen production [71].…”
Section: Adipocytokines In Osteophyte Formationmentioning
confidence: 98%
“…Higher adipocytokine levels were found among women with larger osteophytes (>10 mm) than in those with no or smaller osteophytes (<10 mm) [70]. Visfatin has been also found to influence osteoblasts proliferation and type II collagen production [71].…”
Section: Adipocytokines In Osteophyte Formationmentioning
confidence: 98%
“…Several groups have shown that PBEF interacts with the insulin receptor (8-10); however, this notion remains controversial (11,12), and it may be that PBEF signals through an alternative signaling route. It is also unlikely that this signaling effect is attributable to the endotoxin that may be present in PBEF preparations, since coincubation with polymixin B shows no abrogation of PBEF signaling (6,10,13).In vitro activation of signaling pathways by PBEF has been shown to regulate the expression of metalloproteinases, chemokines, and cytokines (6,7,(9)(10)(11)(12), but the in vivo contribution of this mediator of arthritis progression remains unclear. The recently developed small molecule inhibitor APO866 has been shown to act as a competitive inhibitor of PBEF/NAMPT activity by inhibiting binding of its natural substrate, nicotinamide (14,15).…”
mentioning
confidence: 99%
“…Several groups have shown that PBEF interacts with the insulin receptor (8)(9)(10); however, this notion remains controversial (11,12), and it may be that PBEF signals through an alternative signaling route. It is also unlikely that this signaling effect is attributable to the endotoxin that may be present in PBEF preparations, since coincubation with polymixin B shows no abrogation of PBEF signaling (6,10,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DNA and protein synthesis assay DNA and protein synthesis were assessed using scintillation counting to measure the incorporation of [ 3 H]thymidine (7.4×10 4 Bq/mL) or [ 3 H]leucine into DNA or protein, respectively, as previously described [29][30][31] . Briefly, cells were plated at a density of 2×10 4 /well in 24-well plates, cultured in growth medium and treated with vehicle controls, 5−20 mmol/L TAU, 1−10 mmol/L LC or 20 mmol/L TAU+10 mmol/L LC for 48 h. Then, the plates were washed with PBS, and 10% trichloroacetic acid solution was added to the wells to precipitate the DNA and protein.…”
Section: Methodsmentioning
confidence: 99%